Spatiotemporal trends of ischemic stroke burden attributable to PM2.5 from 1990 to 2021 - Lu, Yunyan; Mao, Yu; Liu, Weiguo; Lan, Tian; Lan, Gaochen (Frontiers in Public Health, 2025)
BackgroundTo evaluate the spatiotemporal variation in ischemic stroke attributed to particulate matter 2.5 (PM2.5) on global, regional, and national scales from 1990 to 2021 is essential for mitigating air pollution and controlling ischemic stroke.MethodsThe death and disability-adjusted life years (DALYs) were extracted from the Global Burden and Disease Study (GBD) 2021. We utilized joinpoint regression and decomposition analysis to assess PM2.5 exposure and pinpoint high-risk areas.ResultsIn 2021, PM2.5 caused approximately 0.90 million mortality and 18.29 million DALYs due to ischemic stroke worldwide. The age-standardized rates (ASRs) of ischemic stroke linked to ambient PM2.5 slightly declined, while those associated with household PM2.5 significantly decreased over the past 32 years. The burden of ischemic stroke attributable to ambient and household PM2.5 exhibited considerable heterogeneity across 204 countries. Household PM2.5 significantly affected ischemic stroke burdens in low Socio-demographic indices (SDI) regions, whereas ambient PM2.5 had a greater impact in middle, high-middle, and high SDI regions. In the regions with an SDI below 0.7, including Southern Sub-Saharan Africa and East, South, and Southeast Asia, there was a positive correlation between SDI and ASRs linked with ambient PM2.5. Notably, in the 65–95 age group, the age-specific rates associated with ambient PM2.5 showed a substantial decline among females, while the rates for males remained relatively stable.ConclusionOur results presented that PM2.5 significantly affects global ischemic stroke burden, particularly among the male population and in low SDI regions. It highlighted the urgency of integrating PM2.5 reduction strategies with ischemic stroke prevention programs.